Answer:
Step-by-step explanation:
55.25x.87=48.07
55.25+48.07=103.32
Answer:
n-13
Step-by-step explanation:
im not up for this bc didn't sleep a lot hope i did ok
Answer:
abc = - 126
Step-by-step explanation:
(2x + 3)(3x - 1) ← expand product using FOIL
= 6x² + 7x - 3 ← in standard form
with a = 6, b = 7, c = - 3
Then
abc = 6 × 7 × (- 3) = - 126
Answer:
no solution
Step-by-step explanation:
hello
![6(x+5)=6x+11\\ 6x+30=6x+11\\ 30=11](https://tex.z-dn.net/?f=6%28x%2B5%29%3D6x%2B11%5C%5C%3C%3D%3E%206x%2B30%3D6x%2B11%5C%5C%3C%3D%3E%2030%3D11)
this is always false so there is no solution
Answer:
12 + 2x
Step-by-step explanation:
<em>simplifying</em><em> </em><em>expression</em><em>:</em>
2(10) + 2(x-4)
2 × 10 = 20
2 × x = 2x
2 × -4 = -8
20 + 2x - 8
20 - 8 = 12
12 + 2x
<em>if you want to simplify it</em><em> </em><em>more</em><em>:</em>
(12/2) + (2x/2)
2(6 + x)
<em>if you want to solve for x:</em>
12 + 2x = 0
(12 - 12) + 2x = (0 - 12)
2x/2 = -12/2
x = -6
hope this helps you!